Representasi Masyarakat Mbojo Dalam Cerpen La Riru Karya Mas’oed Bakry - Randa Anggarista (PENAOQ: Jurnal Sastra, Budaya dan Pariwisata, 2020)
This study used perspective sociology of literary to identify form of local wisdom of Mbojo Tribe in the short story of La Riru by Mas’oed Bakry. This type of research is qualitative research with descriptive analysis method. The data in this research are in the form of text like words, sentences, or discourse in accordance with the formulation of problem. The source of data in this study is short story La Riru by Mas'oed Bakry published by Pusat Pembinaan dan Pengembangan Bahasa in 1984. The results of study showed that in short story of La Riru by Mas'oed Bakry was identified the local wisdom of the Mbojo Tribe community form of locality like linguistic system with the use of Mbojo language; the locality in the art system in the form of horse racing; and locality in the belief system in the form of use witchcraft and teluh; locality in the livelihood system of life through agriculture, plantations, and animal husbandry.